Clinical characteristics of collagenous colitis with linear ulcerations. Issue 1 (7th April 2013) - Saito, Sumio; Tsumura, Takehiko; Nishikawa, Hiroki; Takeda, Haruhiko; Nakajima, Jun; Kanesaka, Takashi; Matsuda, Fumihiro; Sakamoto, Azusa; Henmi, Shinichiro; Hatamaru, Keiichi; Sekikawa, Akira; Kita, Ryuichi; et al.
Abstract : Background: The relationship between the thickness of subepithelial collagen bands (CB) and the development of linear ulcerations (LU) in collagenous colitis (CC) remains unclear. The aim of the present study was to compare the clinical and pathological features, including the thickness of CB, in CC patients with and without LU. Patients and Methods: Twenty‐five patients with CC diagnosed by pathological examination of biopsy specimens were analyzed. Eleven patients with LU (LU group) and 14 patients without LU (non‐LU group) were compared. Results: Ten patients in the LU group and seven in the non‐LU group were taking lansoprazole ( P  = 0.038). Seven patients in the LU group and one in the non‐LU group were taking non‐steroidal anti‐inflammatory drugs (NSAIDs) ( P  = 0.004). All LU were locatedin the transverse or left colon. Patients in the LU group were older than those in the non‐LU group ( P  = 0.015). CB were significantly thicker in the LU group than in the non‐LU group (mean ± SD, 40 ± 21 μm vs 20 ± 11 μm, P  = 0.004). Multivariate analysis showed that NSAIDs use (odds ratio, 19.236; 95% confidence interval, 1.341–275.869) and CB thickness (odds ratio, 0.893; 95% confidence interval, 0.804–0.999) were independently associated with the development of LU. Conclusion: Use of lansoprazole and NSAIDs, thick CB, and advanced age are associated with the development of LU in CC patients.